Green telecommunication - a way forward for green world. (2018) - Khan, Angshuman; Aditya, Amitava
In the field of science, every node of technical application is driven by electricity especially if telecommunication field is concerned and one cannot ignore the harmful effect of greenhouse gases generated from these processes. If green technology is adopted, then reduction in power loss is possible. 'Greening of Telecommunication' is the major breakthrough of power consumption, independent of any application which accounts for the fuel efficient equipment as well as eco-friendly designs of telecommunication networks and also disposal of tele-wastes. Term 'Green' taken in common with every word like codes, power amplifiers, electronics and antennas, shows the road towards green telecom. In this paper, a quantity of work has been done to come out with the re-analysation of green telecommunication which associates the disadvantages of state of the art telecommunication technology and thus gives an idea about the best technology that can be chosen to make the environment go green.